Shaoyao Gancao Decoction: a comprehensive review of modern clinical applications and underlying pharmacological mechanisms - Hong, Du; Xiao, Ying (Frontiers in Pharmacology, 2025)
Shaoyao Gancao Decoction, a classic formula from Zhang Zhongjing in the Han Dynasty, has the effects of regulating the function of the liver, relieving spasm and stopping pain. Traditionally, it is used to treat pain syndromes related to “stiffness and spasm of tendons and vessels”, such as abdominal pain, muscle spasm and neuralgia. Modern studies have shown that this formula has shown significant clinical efficacy in neurological diseases (such as neuralgia and neurodegenerative diseases), digestive system diseases (such as irritable bowel syndrome and gastric spasm), gynecological diseases (such as dysmenorrhea and endometriosis), and adjuvant treatment of tumors (such as pain management after chemotherapy). Its core action mechanism involves multi-target regulation, including inhibiting central nervous excitability, regulating calcium ion channels, inhibiting the release of inflammatory factors, and directly relaxing smooth muscles. This paper summarizes the current clinical applications and pharmacological advances of the Shaoyao Gancao Decoction, while exploring its application potential in emerging fields, aiming to achieve a modern breakthrough and new clinical applications of this traditional compound prescription.